(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Breast cancer in all parts of the world begins to be seen at about 20 years of age. Afterward, age specific incidence steadily rises until the menopause when geographic differences begin to be seen. In the developing world, a flattening and then a decline occur about 10–15 years after the menopause. In developed countries, the age specific incidence accelerates after the menopause, and at age 70 and above doubles that seen at 45–49 years old. Methodology: A descriptive design study was accomplished at teaching hospitals in Babylon province. The study aimed to assess the knowledge and attitudes of the women toward the breast self- examination by the application health belief model from 25th November/ 2018 to 13th June/ 2019. A non-probability “convenient sample” of (250) women were selected from outpatients of the main teaching hospitals of the hilla city. The researcher selected 10% from the number of visitors prior to the month of data collection from each of the three hospitals. Results: The results of the present study show that the demonstrates the distribution of women according to their knowledge about breast self-examination items. With regard to their knowledge reported (Do not know) that puberty as the age of initiation of BSE, it should be done monthly and it should be done five days after menses (59.1%),(61.6%),(70.8%) respectively. Item (1) only reported fair assessment. Conclusions:. Study focuses on clarifying the knowledge and attitudes of women regarding breast self examination according to health belief model in hilla city hospitals.